EXAMINING THE ETHICAL PERCEPTIONS OF ACCOUNTING STUDENTS IN PREPARING FINANCIAL STATEMENTS - Ebrit, Firna; Tenriwaru, Tenriwaru; Saleh, Musliha (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
ABSTRACT Purpose – This study aims to determine the perceptions of accounting students on the ethics of preparing financial statements Design/methodology/approach – The type of data in this study is primary data with the data collection technique used is a questionnaire. The research sampling technique used simple random sampling. Findings – The results showed that there was no difference in the perceptions of accounting student class 2018 and accounting student class 2019 regarding earnings management factors, disclosure of sensitive information, costs and benefits, and accountability. There are differences in the perceptions of accounting student class 2018 and accounting student class 2019 about the factor of misstatement. This is because accounting student class 2018 have a lower tendency to misstate financial statements compared to accounting student class 2019. Originality – The samples in this study were 300 respondents, 150 students from class 2018 and 150 students from class 2019. Keywords: Earnings Management, Misstatement, Disclosure of Sensitive Information, Costs and Benefits, Accountability Paper Type Research Result